IMPROVING STUDENTS’ READING COMPREHENSION THROUGH CONTEXT CLUES STRATEGY AT THE EIGHTH GRADE OF SMP DHARMA WANITA MEDAN - Apriliyanti, Apriliyanti; Tarigan, Karisma E.; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
Reading is one of the four language skills in English, they are listening, speaking, reading and writing. Students get bored with reading and it is very difficult for them to work with it because they do not understand how to comprehend a reading material. Thus, they need some ways or strategy which could help studentsâ€™s reading comprehension on narrative text. The teacher should be creative to search for interesting strategy to teach reading comprehension on narrative text. Context Clues strategy can help the students to understand a narrative text. The objectives of this study to find out the studentsâ€™ reading comprehension by Context Clues strategy. The subject of this study were the eighth grade students of SMP Dharma Wanita Medan. In conducting this research the writer used Classroom Action Research (CAR) as the method of research. The test was used to gather the quantitative data. Based on the finding of this study, it showed in pre-test only 3 students (10%) who passed KKM (the Mastery Minimum Criteria), andÂ post test 27 students (90%). The result of this research revealed that there was a significant improvement of the studentsâ€™ achievement in the post test. This improvement was shown by the comparison between the mean scrore of pre-test (47,26), and post test (80.33). Furthermore, the students were interested in Context Clues Strategy, it can be seen from their full attention during the teaching learning process. Therefore, Context Clues Startegy was effective strategy in helping students to improve their reading comprehension especially in narrative text.